Analysis of the Impact of the Covid-19 Pandemic on the Growth of Non-Performing Loans in Indonesian Banking - Rafida Khairani; Kevin Stephan; Jerico Prince Wijaya; Charolina Charolina; Anggita Putri (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
This paper aims to clarify the determinants of the movement of inon-performing loans in the Indonesian banking sector and the impact of the iCOVID i19 pandemic on them. iTo this end, secondary data is obtained from the ministry of iHealth and the financial services authority I (OJK), each consisting of i47 data samples that have undergone different most it analyzes. iThe analysis used the inon-performing loan variable and the iCOVID19 pandemic variable. the results of the data analysis are how that iCOVID19 has is a significant impact on inon-performing loans, and the iCOVID19 variable can be used as an external indicator of the increase in inon-performing loans by Indonesian banks. It has been shown that there is a significant positive correlation between non-performing loans and the country's economic situation.